Effects of Educational Intervention Pertaining to Knowledge, Beliefs, Barriers and Practices on Breast Cancer Screening Behaviors Among Teachers in Selangor, Malaysia - Parsa, Parisa (2008)
Breast cancer (BC) is the leading cause of cancer death among Malaysian women. Early detection of breast cancer can play an important role in reducing cancer morbidity and mortality. However participation of women in breast cancer screening (BCS) is low in Malaysia. Studies have shown greater risk of breast cancer among women teachers compared to other occupations. The objective of this randomised controlled trial study was to develop and evaluate the effect of an educational intervention to improve knowledge, beliefs, barriers and practices on breast cancer screening among female secondary school teachers in Selangor, Malaysia. A multi-stage random sampling was used for selection of secondary schools in Selangor (4 control schools and 4 intervention schools). All female teachers in the selected schools were invited to participate in the study with informed consent form. Baseline data were collected from 237 (52%) teachers on socio-demographic background, knowledge, beliefs and practices on breast cancer screening. A translated, reliable and valid tool adapted from Champion’s Health Belief Model was used to determine women’s perceptions on BC and BCS. An educational intervention of four months duration comprised a one day seminar supported by an educational model, presentations, brochures, telephone follow-up motivation sessions, and practical demonstration on breast self examination (BSE) and clinical breast examination (CBE) techniques. The control group received all of the informational material after the completion of the study. To evaluate the effect of the intervention data were collected at baseline, immediately, one month and four months after intervention for both groups. Descriptive and multivariate statistics were used for analysing the data using SPSS version 14. The mean age of participants was 37.8 years (SD=7.2) and majority of them were Malay (84%), married (88%) with tertiary education (90%). After intervention, there was a significant increase in the mean score of knowledge (20.7-28.3, p<0.001), beliefs (215.2-225.1, p<0.001) and proportion of BSE (53.4%-87%, p<0.001), CBE (23.3%-37%, p<0.01) and mammography practices (3.4%-10.3% p<0.01,) over the four months follow up in the intervention group. Lack of knowledge (45%- 15%, p<0.001), being busy (37%-28%, p<0.01) and not interested (7%-2%, p<0.01) were the most common barriers to BCS before intervention but these decreased significantly after intervention. Grounded Health Belief Model (HBM) constructs significantly increased for perceived susceptibility, seriousness, confidence and benefits of mammography and decreased in barriers for BSE and mammography was observed in the intervention group but HBM did not predict the BCS behaviours. The logistic regression model showed that change in knowledge score was the predictor of the uptake of BCS practices. The change in knowledge score on risk factors of BC (OR=1.663), screening methods (OR=1.145) and symptoms of BC (OR=1.729) were predictors of BSE, CBE and mammography utilization, respectively. With the exception of a significant change in BSE practice (58.7%-77.9%, p<0.001) the control group showed no significant improvement in all other aspects. These results provide evidence for the effectiveness an educational intervention using a multi-component approaches in promoting breast cancer screening knowledge, beliefs and practices within an educated group as tteachers represent a large portion of educated women in Malaysia. This study suggests that women’s knowledge on BCS can improve breast cancer screening behaviors. In addition availability and affordability of screening services and their cost need to be addressed for promoting breast cancer screening behaviors in Malaysian women.